P127 Is there a need for pelvic ultrasound within an integrated sexual health service?. (8th June 2017) - Pinto-Sander, Nicolas; Rela, Mariam; Yarrow, Kate
Abstract : Introduction: Sexual health services see a number of women who once infection is excluded, may require the use of pelvic ultrasound to aid diagnosis. Without in-house scanning facilities, they often end up on a convoluted route involving several appointments across clinical specialities. Methods: This observational study examined two consecutive years of referrals for pelvic ultrasounds from a busy integrated sexual health service, where in-house scanning was not available. Information from referrals to radiology was gathered from an imaging database where indication and outcomes were analysed from scan reports. Results: 190 patients were scanned with a mean age of 31. 184/190(97%) were outpatients. 79/190(42%) were scanned for pelvic pain, and 42/190(22%) for coil related concerns. 141/190(74%) of scans had normal findings. Of coil related referrals, only 1/42(2%) needed intervention. 19/190(10%) of pelvic ultrasounds had incidental findings not requiring follow up, and 30/190(16%) had findings requiring intervention or follow up. Discussion: In this study, all coils with 'lost threads' were found to be intrauterine – and therefore could be managed within an integrated sexual health service. Only a small number of those scanned needed onward referral or follow-up. With scanning expertise and resources, patients would be seen more quickly, with a reduction in appointments and fewer referrals. This would result in improved patient satisfaction and reduced costs to the NHS. The set-up costs would be offset in the long-term by keeping patients out of the acute setting.